2007
DOI: 10.1111/j.1447-0594.2007.00391.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying interacting predictors of falling among hospitalized elderly in Japan: A signal detection approach

Abstract: Falling is a complex phenomenon that involves interaction of multiple risk factors. The authors analyzed factors related to falls in a geriatric hospital to elucidate interaction of multiple risk factors for falls in elderly inpatients. Subjects were 364 patients (mean age, 81.7; women 76.7%) who were aged 60 years and over and had been hospitalized for more than 6 months between April 2000 and March 2001. A signal detection model was used to identify baseline variables that best divided the sample into subgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Lower OLS time was known to be a potent risk factor for falls independent of already‐known risk factors, 15–19 and falls in elderly causes bone fractures with high probability. In addition, we identified short OLS time as an independent factor for reduced SOS.…”
Section: Discussionmentioning
confidence: 99%
“…Lower OLS time was known to be a potent risk factor for falls independent of already‐known risk factors, 15–19 and falls in elderly causes bone fractures with high probability. In addition, we identified short OLS time as an independent factor for reduced SOS.…”
Section: Discussionmentioning
confidence: 99%
“…Although confusion has long been recognized as a risk factor for falls, risk factors among confused patients have to our knowledge not been studied 3,4,22 . While there is evidence that multidisciplinary interventions can have an effect in reducing falls in cognitively‐intact patients, preventing falls among confused patients remains a challenge 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Among the clinical characteristics, the fall rate differed according to the clinical unit to which the patient had been admitted, activity level, pain, surgery, sleeplessness, and the presence of skin, digestive, respiratory or neuromuscular disorders. This can be understood in the same context as the study of Nabeshima et al ., which used factors related to falls in a geriatric hospital to elucidate the interactions between multiple risk factors for falls in elderly inpatients, and the study of Mamun and Lim, which demonstrated that the factors affecting falls in the elderly are balance problems, blood pressure drop on standing, medication and muscle weakness.…”
Section: Discussionmentioning
confidence: 99%